DIFFERENCES IN GERMINATION AND FLOODING TOLERANCE AMONG CORN VARIETIES - Correia, Daniela Marques; Almeida, Ramonn Diego Barros de; Silva, Jóice Azeredo; Rodrigues, Natália Fernandes; Ferreira, Vitor Francisco; Huther, Cristina Moll; Hamacher, Leonardo da Silva; Rigueira, Roberta Jimenez de Almeida; Pereira, Carlos Rodrigues (REVISTA DE AGRICULTURA, 2023)
The present study sought to identify and evaluate the Germination Speed Index (GSI), the differences in growth and pigments in the hybrids Agroceres® (Hybrid AG 8780) and Pioneer® (Hybrid 30F53VYHR) submitted to stress by flooding in the vegetative stage. Two tests were carried out: in Trial I it was verified the GSI in both varieties, where it was found a higher germination tax and velocity for the variety Agroceres® (Hybrid AG8780). In Trial II, the plants that originated from Trial I were imposed to stress by flooding. From 3 DAF (Days After Flooding) it was evaluated: NDVI (Normalized Difference Vegetation Index), height, diameter of stem and visual analysis and, in the end of Trial II it was evaluated the photosynthetic pigment content. In the analysis of growth and photosynthetic pigment content, it was possible to verify that the Pioneer® (Hybrid 30F53VYHR) variety presented a better performance, with less variations when compared to the plants in control treatment, being more suitable for situations of stress by flooding.